Damage Assessment of Two-Way Bending RC Slabs Subjected to Blast Loadings - Haokai Jia; Ling Yu; Guiying Wu (The Scientific World Journal)
Terrorist attacks on vulnerable structures and their individual structural members may cause considerable damage and loss of life. However, the research work on response and damage analysis of single structural components, for example, a slab to blast loadings, is limited in the literature and this is necessary for assessing its vulnerability. This study investigates the blast response and damage assessment of a two-way bending reinforced concrete (RC) slab subjected to blast loadings. Numerical modeling and analysis are carried out using the commercial finite element code LS-DYNA 971. A damage assessment criterion for the two-way bending RC slab is defined based on the original and residual uniformly distributed load-carrying capacity. Parametric studies are carried out to investigate the effects of explosive weight and explosive position on the damage mode of the two-way RC slab. Some design parameters, such as the boundary conditions and the negative reinforcement steel bar length, are also discussed. The illustrated results show that the proposed criterion can apply to all failure modes. The damage assessment results are more accurate than the ones due to the conventional deformation criterion.